Contemporary management of clival chordomas. Issue 2 (April 2015) - Campbell, Raewyn G.; Prevedello, Daniel M.; Filho, Leo Ditzel; Otto, Brad A.; Carrau, Ricardo L.
<x xml:space="preserve">Abstract</x> Purpose of review Clival chordomas are rare malignant tumors associated with a poor prognosis. In this article, we review the current literature to identify a variety of strategies that provide guidelines toward the optimal management for this aggressive tumor. Recent findings Molecular disease, particularly, the development of characterized chordoma cell lines, has become one of the new cornerstones for the histological diagnosis of chordomas and for the development of effective chemotherapeutic agents against this tumor. Brachyury, a transcription factor in notochord development, seems to provide an excellent diagnostic marker for chordoma and may also prove to be a valuable target for chordoma therapy. Aggressive cytoreductive surgery aiming for gross total resection with maintenance of key neurovascular structures, followed by proton beam or hadron radiation, provides the best local recurrence and overall survival rates. Summary Clival chordomas are locally aggressive tumors that are challenging to treat because of their unique biology, proximity to key neurovascular structures and poor prognosis. Currently, chordomas are optimally managed with aggressive surgery, whilst preserving key structures, and postoperative radiation in a multidisciplinary setting with an experienced team. The advancement of molecular techniques offers exciting future diagnostic and therapeutic options in the management of chordomas.